Morphological characters of antennae Sumatran Longipeditermes (Termitidae, Nasutitermitinae) - . Syaukani (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Among three genera of open-air processional column termites in Sumatra, Longipeditermes is the most commonly observed. Their workers make food balls at the foraging sites and carry them back to the nest. This genus has a black color, long legs and antennae. Antenna is much paler than head capsule in coloration, with the basal segments (first and second) are generally darker than subsequent ones; antenna is long with fourteen segments; third segment is twice as long as fourth or more. Their distribution in Sumatra is mentioned briefly